Subimperialismo no Brasil e mobilidade da força de trabalho : considerações referentes à região sul e o Mercosul - Ponce Martins, Alexandre Luís (2016)
In this research whose objective is to look for understanding dynamics of labor force mobility inside some states of Brazil like as Rio Grande do Sul, Paraná e Santa Catarina, and with their border countries Argentina, Paraguay and Uruguay, founder members of MercoSur and also to check information related to economics data between Brazil and this economic block to try to link Brazilian under-imperialist possible actions in this juncture. We justify this research by the premise of unequal development and this combine with the generation of perverse dialectics spaces, identifying those aspects means enormous significance to solve those submitted actors and their enfranchisement by the inequality of the capital. This objective demanded a data series referring to natural, physics, and geo-economics characteristics of the study area. We have a highlight in rescue historical relations among those countries as well as the considered states of the Brazilian Federation. By this way it is possible to justify the capitalist interests in a determined area and its attraction to the inhabitants to promote mobility around the jobs, perspective proved with an analysis methodology used, i.e, dialectic historical materialism and the geographic criticism. From a bibliographic point of view was made a review of concepts related to this job agenda, i.e, the mobility of workforce, territory, border, imperialism, hegemony, and under-imperialism. It was sought to the relevant data for this study as well as immigration, admission, and deportation of foreign people, balance of trade, the main imported and exported products. The data found were charted and presented in charts to an easy comprehension of the results. Finally, we point the outcome obtained as result of the research was satisfactory because the objectives were joined and showed a capitalist logic in the under-imperialist format in several aspects.